STRATEGI PEMANDUAN TERPADU UNTUK MENCAPAI KESETIMBANGAN EKONOMI DAN KEAMANAN DI SELAT MALAKA DENGAN PENDEKATAN SSM - TSNB Hutabarat; M. Syamsul Ma’arif; Nimmi Zulbainarni; Purnomo Yusgiantoro (School of Business, Bogor Agricultural University (SB-IPB), 2021)
One of the main issues facing the Government in Malacca Strait is the security and safety issue, which threatens the users of sea transportation service and potentially interferes with the business operation. In fact, most of the international distribution lines pass through the Malacca Strait, making it the busiest strait in the world. On the other hand, the high cost of maintaining security and safety in the area burdens the government. Hence, this research aims to develop a strategy in handling the sea transportation system to achieve the equilibrium between economic efficiency and the government's effectiveness in maintaining the security and safety of the shipping traffic in Malacca Strait. This study is a problem solving-based research using Soft System Methodology. As a result, the integrated piloting strategy has been developed as a recommendation to be implemented. With this strategy, the ships that pass through the Malacca Strait are advised to adopt integrated piloting. The pilots and the security guards would be on board and safely and securely help the ship pass through the Malacca Strait. By that, safety and security would be guaranteed, and the business objectives would be achieved. Keywords: malacca strait, maritime study, sea transportation, soft system methodology